Changing Clinical Practice: Evaluation of Implementing Recommendations for Opportunistic Salpingectomy in British Columbia and Ontario. Issue 6 (July 2018) - Lander, Bryn; Wilcox, Elizabeth; McAlpine, Jessica N.; Finlayson, Sarah J.; Huntsman, David G.; Miller, Dianne; Hanley, Gillian E.
Abstract : Objective: The aim of the study was to explore the factors that contributed to the adoption of opportunistic salpingectomies (removal of fallopian at the time of hysterectomy or in lieu of tubal ligation) by gynecologic surgeons in British Columbia (where a knowledge translation initiative took place) and in Ontario (a comparator where no knowledge translation initiative took place). We aimed to understand why the knowledge translation initiative undertaken by OVCARE in British Columbia resulted in such a dramatic uptake in opportunistic salpingectomy. Methods: We undertook a qualitative evaluation of clinicians' decisions about whether or not they should adopt the practice of opportunistic salpingectomy based on interviews with gynecologic surgeons in British Columbia and Ontario (n = 28). The analysis draws from the Consolidated Framework for Implementation Research. Results: Regional cohesion combined with practice change information exposure and thought leader support were important in explaining differences in adoption levels between participants. The British Columbian knowledge translation campaign was successful because provincial thought leaders exposed gynecologic surgeons to recommendations through multiple sources within a highly socially cohesive environment wherein clinicians felt pressure to adopt the recommendations. In both provinces, high adopters often believed that the workload and surgical risk associated with the adoption was low and the potential benefit—because of limited ovarian cancer detection and treatment options—was high. Conclusion: This research points to the important role that local professional networks can play in encouraging clinicians to change their practice by creating a cohesive regional environment where clinicians are repeatedly exposed to important information and supported in their practice change by local thought leaders.